A Comparative Budget Requirements for TB program based on Minimum standard of Services (SPM) and Budget Realization: an Exit Strategy Before Termination of GF ATM - Setiawan, Ery; Sucahya, Purwa K; Thabrany, Hasbullah (Jurnal Ekonomi Kesehatan Indonesia, 2016)
It has become a common issue that the Global Fund (GF) as one of the largest international donors to AIDS, Tuberculosis, and Malaria Program will immediately stop the funding. Data shows that in 2009 GF ATM support reached 88,8% while APBN funding just cover 11,2% of the total budget needed. However, APBN budget for ATM programs was significantly increased in 2012 which covered almost 30% of the total budget. Eventhough the increasing trend of ATM budget seemed at the central government level, how ever the local governments will hold the key to the sustainability of the post- termination GF ATM Funding